Confirmation of the potential mechanism of pentagamavunon-0 against temporomandibular arthritis using bioinformatic approaches - Dwi Merry Christmarini Robin; Retno Ardhani; Dhania Novitasari; Banun Kusumawardani; Faaza Aulia Rahman; Edy Meiyanto; Nunuk Purwanti (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Non-steroidal anti-inflammatory drugs (NSAID) are widely used in temporomandibular joint osteoarthritis management. However, the side effects of NSAIDs on multiple organs need to be anticipated. Curcumin is known for its anti-inflammatory and analgesic potential, comparable to that of NSAIDs. In a previous study, structurally modified curcumin increased the pharmacological effect and simultaneously reduced the toxicity and side effects of curcumin. Pentagamavunon-0 (PGV-0) is one of the active components synthesized by the structure modification of curcumin. Purpose: In this study, we identify the potential target of PGV-0 on the pathogenesis of temporomandibular arthritis characterized by inflammation. Methods: We used a bioinformatics approach to compare the PGV-0 target with curcumin and diclofenac sodium as controls. We identified overlapping gene targets of bioactive compounds (PGV-0, curcumin, or diclofenac sodium) retrieved from the SwissTargetPrediction and GeneCards platforms, specifically for temporomandibular arthritis. An interaction model among targets was developed using the STRING database and Gene Ontology Panther to expound on the bioactive compound’s function on the key signaling pathway. Finally, we formulated a molecular docking prediction between the bioactive compound and the target protein marker derived from the previous analysis using Molecular Operating Environment tools. Results: This study found that curcumin and PGV-0 targeted different molecular pathways in temporomandibular arthritis compared to diclofenac sodium. Curcumin and PGV-0 shared a similar pathway to curcumin by modulating metalloproteinases (MMPs), especially MMP-9 and MMP-13. Moreover, diclofenac sodium influenced cyclooxygenase metabolism. Conclusion: In this study, PGV-0 targeted metalloproteinase in temporomandibular arthritis pathogenesis. This finding underlines the PGV-0 advantage in preventing metalloproteinase-related tissue damage in temporomandibular arthritis.